Effectiveness Diagnosis of Pulmonary Tuberculosis (TB) in Children Based on Clinical Symptoms - Seshy Tinartayu; Syarrah Tiara Harrini (HM Publisher, 2022)
Background: Diagnosis of pulmonary tuberculosis (TB) in children is still a challenge because the gold standard by examining sputum AFB is difficult. This study aimed to see the effectiveness of diagnosing TB in children based on clinical symptoms. Methods: This study is a retrospective study with a case-control design, and consecutive sampling from the medical records of pediatric TB patients at Panembahan Senopati Hospital, Bantul for the period January 2014 - December 2016. The total population is 90, and the sample is 73. Children diagnosed with a score (score 6) are in the control group (n=30), while children with a diagnosis score of <6 were diagnosed with pulmonary TB based on clinical symptoms, we categorized them into the case group (n=43). Results: There was no difference in gender, age, and group domicile. However, there was no significant difference in nutritional status (malnutrition), long cough, and chest X-ray. The difference between the two groups was found in symptoms of fever and enlarged lymph nodes. Also, it was found in TB contacts and the Mantoux test but this could be a recall bias because in the diagnosis group this is rarely done. The sequential scoring parameters from the most common were chest X-ray, malnutrition, cough, enlargement of lymph nodes, fever, contact TB, and the Mantoux test. Improvement of symptoms (cough, fever, lymph nodes, and chest X-ray) after 6 months of therapy occurred 100% in both groups. Conclusion: The diagnosis of TB in children based on clinical symptoms can be used as an effective alternative.